Charcoal in Kunlun Mountains loess: Implications for environment change and human activity during the middle Holocene - Pan, Yanfang; Mu, Guijin; Gao, Cunhai; Behling, Herman; Liu, Dexin; Wu, Guangyang (Frontiers in Earth Science, 2023)
Loess sediment charcoal records are used in paleoecological analyses to reconstruct fire history and human activities. The Tarim Basin is bordered to the south by the Kunlun Mountains, where eolian silt or loess is extensive and has continued to be deposited in modern times. In this study, we conducted multiple analyses of a 720–cm–thick loess section (KLA) at 3516 m elevation in the Kunlun Mountains to reconstruct the middle Holocene vegetation history in northern China. Our palynological, charcoal, and grain-size data reveal a slightly drying trend with notable moisture fluctuations in the Kunlun highland since ~4.9 kyr (1 kyr = 1000 cal yr BP). At approximately 4.1, 2.0 and 1.0 kyr, the climate became more arid; the intervals of 4.0–3.2, 2.4–1.9 and 0.7–0.5 kyr were relatively wet periods. Some sand activity phases in the southern margin of the Taklimakan Desert are recorded around 4.0–3.5, 2.5–2.3 and 1.2–0.7 kyr. Stronger human activities commenced at approximately 2.0 kyr. On the basis of sedimentary charcoal concentrations and regional paleoclimatic and archaeological records, we propose that micro charcoal (<50 μm) originated from the Tarim Basin, reflecting human activity in the basin. Macro charcoal (>50 μm) is suitable for reconstructing Kunlun highland fire events. We suggest that increased anthropogenic activities such as agriculture, construction, and wars played an important role in land degradation and abandonment of ancient cities in the southern Tarim Basin. Our results provide new insights into the role of humans in the ecological evolution of inland arid areas in China during the middle Holocene.